Diagnostic Accuracy of Imaging Modalities and Injection Techniques for the Diagnosis of Femoroacetabular Impingement/Labral Tear: A Systematic Review With Meta-analysis. (September 2017) - Reiman, Michael P.; Thorborg, Kristian; Goode, Adam P.; Cook, Chad E.; Weir, Adam; Hölmich, Per
Background: Diagnosing femoroacetabular impingement/acetabular labral tear (FAI/ALT) and subsequently making a decision regarding surgery are based primarily on diagnostic imaging and intra-articular hip joint injection techniques of unknown accuracy. Purpose: Summarize and evaluate the diagnostic accuracy and clinical utility of various imaging modalities and injection techniques relevant to hip FAI/ALT. Study Design: Systematic review with meta-analysis. Methods: A computer-assisted literature search was conducted of MEDLINE, CINAHL, and EMBASE databases using keywords related to diagnostic accuracy of hip joint pathologic changes. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were used for the search and reporting phases of the study. Quality assessment of bias and applicability was conducted using the Quality of Diagnostic Accuracy Studies (QUADAS) tool. Random effects models were used to summarize sensitivities (SN), specificities (SP), likelihood ratios (+LR and –LR), diagnostic odds ratios (DOR), and respective confidence intervals (CI). Results: The search strategy and assessment for risk of bias revealed 25 articles scoring above 10/14 on the items of the QUADAS. Four studies investigated FAI, and the data were not pooled. Twenty articles on ALT qualified for meta-analysis. Pretest probability of ALT in the studies in this review was 81%( 72%-88%), while the pretest probability of FAI diagnosis was 74% (95% CI, 51%-91%). The meta-analysis showed that computed tomography arthrography (CTA) demonstrated the strongest overall diagnostic accuracy: pooled SN 0.91 (95% CI, 0.83-0.96); SP 0.89 (95% CI, 0.74-0.97); +LR 6.28 (95% CI, 2.78-14.21); –LR 0.11 (95% CI, 0.06-0.21); and DOR 64.38 (95% CI, 19.17-216.21). Conclusion: High pretest probability of disease was demonstrated. Positive imaging findings increased the probability that a labral tear existed by a minimal to small degree with the use of magnetic resonance imaging/magnetic resonance angiogram (MRI/MRA) and ultrasound (US) and by a moderate degree for CTA. Negative imaging findings decreased the probability that a labral tear existed by a minimal degree with the use of MRI and US, a small to moderate degree with MRA, and a moderate degree with CTA. Clinical Relevance: Although findings of the included studies suggested potentially favorable use of these modalities for the diagnosis of ALT and FAI, our results suggest that these findings have limited generalizability and clinical utility given very high pretest prevalence, large confidence intervals, and selection criteria of the studies. Registration: PROSPERO Registration #CRD42015027745.